The Effect of Debt To Equity Ratio (DER) and Cash Ratio on Profitability in Pharmaceutical Companies Listed on the Indonesian Stock Exchange for the 2018-2022 Period - Septiani Nalurita; Raden Rijanto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to examine the relationship between cash ratio, debt to equity ratio, and profitability. This research combines quantitative techniques with an associative descriptive approach. Over a period of five years, samples of financial report data from eleven companies were collected using a census approach. The Chow and Hausman tests are used in selecting the panel data regression model. The data processing tool used is called E-Views 12. The selected model is used to confirm conventional wisdom. This research involves model selection, panel data regression analysis, coefficient of determination, and testing its significance using t and F tests. The results of the research show that the Debt to Equity Ratio (DER) and Cash Ratio have a significant influence on profitability. It was determined that a random effects model was appropriate. The debt to equity ratio (DER) and cash ratio both have a positive effect on profitability, based on the findings of the significance test. However, the impact on profitability is slightly higher